2022
DOI: 10.3389/fonc.2022.1034750
|View full text |Cite
|
Sign up to set email alerts
|

Gou Qi Zi inhibits proliferation and induces apoptosis through the PI3K/AKT1 signaling pathway in non-small cell lung cancer

Abstract: BackgroundGou Qi Zi (Lycium barbarum) is a traditional herbal medicine with antioxidative effects. Although Gou Qi Zi has been used to prevent premature aging and in the treatment of non-small cell lung cancer (NSCLC), its mechanism of action in NSCLC remains unclear. The present study utilized network pharmacology to assess the potential mechanism of action of Gou Qi Zi in the treatment of NSCLC.MethodsThe TCMSP, TCMID, SwissTargetPrediction, DrugBank, DisGeNET, GeneCards, OMIM and TTD databases were searched… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 86 publications
0
4
0
Order By: Relevance
“…[33] TCM also acts on Akt1 in the treatment of NSCLC, like Lycium barbarum. [34] Tumor necrosis factor, also known as TNF, is widely expressed in NSCLC, it could be a biomarker in NSCLC. [35] In this study, we also analyzed the BP, MF, CC, and pathways involved in the potential targets of kiwi root against NSCLC, KEGG analysis showed that PI3K-AKT and MAPK signaling pathway may be the central pathways in NSCLC therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[33] TCM also acts on Akt1 in the treatment of NSCLC, like Lycium barbarum. [34] Tumor necrosis factor, also known as TNF, is widely expressed in NSCLC, it could be a biomarker in NSCLC. [35] In this study, we also analyzed the BP, MF, CC, and pathways involved in the potential targets of kiwi root against NSCLC, KEGG analysis showed that PI3K-AKT and MAPK signaling pathway may be the central pathways in NSCLC therapy.…”
Section: Discussionmentioning
confidence: 99%
“…[ 33 ] TCM also acts on Akt1 in the treatment of NSCLC, like Lycium barbarum . [ 34 ] Tumor necrosis factor, also known as TNF, is widely expressed in NSCLC, it could be a biomarker in NSCLC. [ 35 ]…”
Section: Discussionmentioning
confidence: 99%
“…In a case where single therapy may have little or no effect, holistic integrative medicine may be utilized (32). Furthermore, a combination of multiple therapies, including conventional therapy, targeted therapy, immunotherapy, and complementary and alternative medicines, such as TCM (33), are a relatively newer route for the treatment of tumor and metastasis in the last 5 years. Research has showed that Qianjinweijing decoction combined with chemotherapy improves the quality of life of patients, and prolongs the survival time of patients with advanced NSCLC (34).…”
Section: Discussionmentioning
confidence: 99%
“…L. barbarum has been used in traditional Chinese medicine for its ability to nurture the liver, improve blurred vision, relieve headaches, and alleviate abdominal pain [ 7 ]. Studies have demonstrated that L ycium barbarum polysaccharide (LBP) possesses multiple preventive and ameliorative effects, including antioxidant, anticancer, lipid-lowering, and lung lesion reduction [ [8] , [9] , [10] ]. Studies have shown that LBP has anti-inflammatory effects.…”
Section: Introductionmentioning
confidence: 99%